Terahertz dielectric resonator antennas for high speed communication and sensing : from theory to design and implementation - Yaduvanshi, Rajveer S. (IET telecommunications series ;, 2021)
This book covers the theory, modelling, design and implementations of Terahertz Dielectric Resonator Antenna technologies at microwave, terahertz or optical frequencies for future applications in wireless high-speed communication, wireless personal communication and sensor networks. Case studies with prototype models are included